Characterization and antibacterial activity of the essential oil obtained from the leaves of Baccharis coridifolia DC against multiresistant strains. (August 2020) - Freitas, Priscilla Ramos; de Araújo, Ana Carolina Justino; dos Santos Barbosa, Cristina Rodrigues; Muniz, Debora Feitosa; Rocha, Janaina Esmeraldo; de Araújo Neto, José Bezerra; da Silva, Maria Milene Costa; Silva Pereira, Raimundo Luiz; da Silva, Luiz Everson; do Amaral, Wanderlei; Deschamps, Cicero; Relison Tintino, Saulo; et al.
Abstract: Essential oils are secondary metabolites with immense pharmacological potential.These substances are abundantly produced by plants of the family Asteraceae, such as Baccharis coridifolia . Previous studies have demonstrated that this species has pharmacological properties that make it a promising source of new antibacterial agents. Therefore, the present study aimed to evaluate the antibacterial and antibiotic-modulating activity of Baccharis coridifolia essential oil against multidrug-resistant (MDR) strains. The phytochemical analysis was carried out by gas chromatography coupled to Mass Spectroscopy (GC/MS), and realized the Minimum Inhibitory Concentation (MIC) and antibiotic-modulation from the microdilution method in 96-well plates. It was revealed the presence of germacrene D (23.7%), bicyclogermacrene (17.1%), and (E)-caryophyllene (8.4%) as major components. The minimum inhibitory concentration of essential oil against strains of Pseudomonas aeruginosa (512 μg/mL) and Staphylococcus aureus (128 μg/mL) demonstrated clinically relevant antibacterial activity. In addition, the combination of subinhibitory doses of the oil with conventional antibiotics showed synergism, indicating potentiation of the antibacterial effect. In conclusion, the essential oil of Baccharis coridifolia (EOBc) presented antibacterial and antibiotic-modulating activities that place this species as a source of molecules useful in the fight against bacterial resistance. Highlights: The EOBc has antibacterial activity against MDR strains. The oil potentiated the action of aminoglycosides against MDR bacteria. The antibacterial activity possibly due the higher concentration of germacrene D compound in EOBc.